2011
DOI: 10.1590/s0074-02762011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Spoligotyping of clinical Mycobacterium tuberculosis isolates from the state of Minas Gerais, Brazil

Abstract: We performed spoligotyping on 114 strains of the Mycobacterium tuberculosis (Mtb) complex that had been isolated from patients in Minas Gerais Health Units during 2004. A total of 82/114 (72%) clinical isolates were clustered and 32/114 (28%) were unique. Seven shared types containing nine strains were newly created. A total of nine patterns corresponded to unreported orphan strains, as evaluated against all of the strains recorded in the SITVIT2 proprietary database in the Institut Pasteur de la Guadeloupe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
10
1
1
Order By: Relevance
“…This sublineage appeared to be most common in Brazil (46%), Venezuela (53%), and Peru (28.3%). In the three countries that share borders with Colombia, the proportion of Haarlem is quite variable; our data shows a proportion of 41% among the studied isolates, in contrast to those seen in Venezuela (5%), Brazil (12%), and Peru (28%) [20][23], [25].…”
Section: Discussioncontrasting
confidence: 64%
“…This sublineage appeared to be most common in Brazil (46%), Venezuela (53%), and Peru (28.3%). In the three countries that share borders with Colombia, the proportion of Haarlem is quite variable; our data shows a proportion of 41% among the studied isolates, in contrast to those seen in Venezuela (5%), Brazil (12%), and Peru (28%) [20][23], [25].…”
Section: Discussioncontrasting
confidence: 64%
“…Mycobacterium tuberculosis is classified into six phylogenetic lineages, each of which can be divided into sublineages [32] . Members of the Euro- American lineages represented by the LAM, H, T, S and X Spoligotyping families, which are genetically closely related are the most common in South America [19] , [20] , [21] and this was confirmed recently also in Brazil [22] and in different states of the country [8] , [43] , [44] , [45] , [46] , [47] [48] , but differences in the frequency of these families are observed, theses difference could also be due to differences in population and immigration history in each region or in period associated genotype frequencies or in differences in sample size. We here confirm the predominance of the Euro-American lineage (also known as lineage 4) with only two isolates classified as Indo-Oceanic lineage (EAI5) and East Asian lineage (Beijing), the first being more prevalent in east Africa, southeast Asia and in south India and the second in east Asia, Russia and South Africa.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies also showed a higher percentage of the T lineage when compared to the H lineage. In particular, Miranda et al (2011) described the lowest percentage of the H lineage (7.0%) in Minas Gerais.…”
Section: Discussionmentioning
confidence: 94%
“…Mendes et al (2011) reported a frequency of 36.1% of LAM among 93 isolates from the metropolitan São Paulo area, and Gomes et al (2011), who provided the first insight into the population structure of TB isolates in Brazil, reported that the lowest percentage of the LAM lineage (35.0%) had been observed among 180 isolates from São Paulo state. Noguti et al (2010) showed the lowest percentage (34.7%) of this lineage in Maringá (93 isolates), and Miranda et al (2011) showed the highest percentage (55.3%) of this lineage in Minas Gerais (114 isolates).…”
Section: Discussionmentioning
confidence: 98%